2020
DOI: 10.1002/ijc.33259
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term trends and recent birth‐cohort‐dependent changes in incidence rates of cutaneous malignant melanoma in Italy

Abstract: In Oceania, North America and north‐western Europe, after decades of increase, cutaneous malignant melanoma (CMM) rates began to stabilise or decline before 2000. Anecdotal evidence suggests that the reversal of the incidence trend is extending to southern Europe. To obtain a formal confirmation, this nationwide study from Italy investigated the incidence trends by birth cohort. Twenty‐one local cancer registries covering a population of 15 814 455 provided incidence data for primary CMM registered between 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 47 publications
1
31
1
Order By: Relevance
“…Among people older than 34 years, annual incidence rates continuously increased until 2018. This age- and time-dependent trend pattern may be explainable by a birth cohort effect that has also been shown in several other populations in European mainland [ 2 , 3 ], Australia [4] , and the U.S. [5] . Memon et al.…”
supporting
confidence: 64%
“…Among people older than 34 years, annual incidence rates continuously increased until 2018. This age- and time-dependent trend pattern may be explainable by a birth cohort effect that has also been shown in several other populations in European mainland [ 2 , 3 ], Australia [4] , and the U.S. [5] . Memon et al.…”
supporting
confidence: 64%
“…Firstly, cancer registration in Italy has been introduced irregularly both in time and space. The implications of, and the potential solutions to, this drawback are discussed in another article 29 . Restricting the analysis to a smaller number of registries with comparable time periods of registration, as we did in this study, is one of the most commonly used approaches 59 …”
Section: Discussionmentioning
confidence: 99%
“…Over the past three decades, the incidence of CMM in Italy has constantly increased 29 . Several local studies have already suggested that this trend has been more pronounced for thin CMM 30,31 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Canada [ 204 ], Italy [ 205 ], and England [ 206 ] there is evidence that the incidence of melanoma is stabilising in younger age groups. The incidence in children aged 10–19 in the United States also decreased from 2000 to 2015 [ 207 ].…”
Section: Human Healthmentioning
confidence: 99%